Strategi Pembelajaran Aktif dengan Penggunaan Perisian Sistem Pakar. - Masood, Mona
The research was conducted with the aim to examine pre-university students' higher order thinking skills with regard to the learning of biology specifically the topic on Cellular Respiration by introducing the use of mastery and cooperative learning strategies. An expert system specifically an online interactive multimedia was developed and used as the delivery method. The system incorporated mastery learning, providing ample enrichment activities before students are able to proceed to a higher unit in the lesson.